The Sensitivity of Consumption to Transitory Income: Estimates from Panel Data on Households - Hall, Robert E.; Mishkin, Frederic S. (Econometrica, 1982)
We investigate the stochastic relation between income and consumption (specifically, consumption of food) within a panel of about 2,000 households. Our major findings are: 1. Consumption responds much more strongly to permanent than to transitory movements of income. 2. The response to transitory income is nonetheless clearly positive. 3. A simple test, independent of our model of consumption, rejects a central implication of the pure life cycle-permanent income hypothesis. The observed covariation of income and consumption is compatible with pure life cycle-permanent income behavior on the part of80 percent of families and simple proportionality of consumption and income among the remaining 20 percent. As a general matter, our findings support the view that families respond differently to different sources of income variations. In particular, temporary income tax policies have smaller effects on consumption than do other, more permanent changes in income of the same magnitude.